2022
DOI: 10.1097/md.0000000000029493
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk of colorectal polyps among the Korean population under 50 years

Abstract: Colorectal cancer is a common cancer; generally, adults aged ≥ 50 years are screened using stool occult blood tests and colonoscopy. However, colorectal adenoma and cancer have been found in patients under the aged of 50, and studies on characteristics and risk factors in young patients are lacking. We evaluated the prevalence and risk factors of colorectal adenoma and cancer in young adults aged under 50 years.We retrospectively analyzed 570 individuals aged under 50 years who underwent colonoscopy at the Hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
1
1
Order By: Relevance
“…[32][33][34] The proportion of patients with polyps and diverticula increased with age, which suggested that age is a significant risk factor for both disorders. 35 Compared to our findings, other studies have shown that these lesions increase with age. 32,36 The chance for colorectal polyps was higher in obese people, so the chance of developing polyps increased with increasing BMI.…”
Section: Number Of Diverticulacontrasting
confidence: 91%
“…[32][33][34] The proportion of patients with polyps and diverticula increased with age, which suggested that age is a significant risk factor for both disorders. 35 Compared to our findings, other studies have shown that these lesions increase with age. 32,36 The chance for colorectal polyps was higher in obese people, so the chance of developing polyps increased with increasing BMI.…”
Section: Number Of Diverticulacontrasting
confidence: 91%
“…CRC usually arises from adenomatous polyps through the adenoma-carcinoma sequence [ 6 ]. In Korea, the prevalence of colorectal adenomas was reportedly 3.2% in individuals aged 19-29 years, 13.8% in those 30-39 years, and 21.1% in those aged 40-49 years [ 7 ]. Risk factors for the development of colorectal neoplasia in individuals younger than 50 years included being male, being older than 45 years, and having a change in bowel habits [ 7 ].…”
Section: Introductionmentioning
confidence: 99%